Class system based on the use of flashcards teaching resources for teaching phrasal verbs - Rambay Salazar, Karen Madeleyne (Machala: Universidad Técnica de Machala, 2023)
Phrasal Verbs play an important role in the English language because they are an essential part of the Anglo-Saxon vocabulary and are frequently used in conversation and writing. This can be a true challenge for Spanish-speaking students. This thesis evaluated the effectiveness of a classroom vocabulary acquisition system based on flashcards. This unique case study took place at the Kichwakunapak Amawta Yachay Intercultural Bilingual Unit in the city of Machala. The study is divided into four chapters, each with a specific purpose. The proposed class system effectively improved learning of phrasal verbs in the English classroom. Chapter one introduces the study's theoretical background. Chapter three proposes the practical contribution of the study: a class system. Finally, chapter four evaluates the effectiveness of this system. The research employed several theoretical methods such as analytic synthesis, historical logic, and systems, supported by hermeneutics as the primary qualitative research method. Chapter two outlines the methods used. From the empirical level, we used an experiment, pedagogical testing, observation, and interviews as part of the research scheme.
Los Phrasal Verbs cumplen con un rol importante en el idioma inglés, ya que son una parte esencial del vocabulario anglosajón y se utilizan con frecuencia en la conversación y la escritura. Esto a su vez puede representar un verdadero desafío para los estudiantes hispanohablantes. En esta tesis, se evaluó la efectividad de un sistema de clases basado en la implementación de flashcards para la adquisición de vocabulario en el aula de inglés. Este estudio de caso único se llevó a cabo en la Unidad Intercultural Bilingüe Kichwakunapak Amawta Yachay de la ciudad de Machala. El sistema de clases propuesto fue efectivo para mejorar el aprendizaje de verbos frasales en el aula de inglés. El trabajo se divide en cuatro capítulos, cada uno con un propósito específico. El capítulo uno presenta el contexto teórico del estudio, el capítulo dos describe los métodos utilizados, el capítulo tres presenta el sistema de clases propuesto, que es el aporte práctico del estudio, y el capítulo cuatro evalúa la efectividad del sistema de clases. En la investigación se emplearon métodos del nivel teórico como el analítico sintético, el histórico lógico y el sistémico, sustentados en la hermenéutica como método fundamental de la investigación cualitativa. Del nivel empírico se emplearon el experimento como esquema de la investigación, la prueba pedagógica, la observación y la entrevista.
Keywords: PHRASAL VERB; FLASHCARD; LEARNING; STUDENT